Changes in physical performance characteristics of female volleyball players during regional division competitions - Karahan, Mustafa; Çolak, Mergül (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
This study aims to examine the seasonal changes in the physical performance of female volleyball players competing in the regional division. Forty-three volunteer female players (age: 22 ± 2.1 years, height: 172.9 ± 4 cm, weight: 61.5 ± 6 kg, experience: 8.8 years) competing in the same group of the regional division of the Turkish volleyball league participated in this study. Players participated in a series of test protocols including the 20m shuttle-run, T-run, 20m sprint, vertical jump, and running anaerobic sprint (RAST) in the beginning, mid, and ending of the 16-week competition season. The results showed that all tested physical performance characteristics of the players improved significantly in both the first and second periods of the competition season. However, the improvements in the first period were significantly higher than in the second period for VO2max (4.7 vs 1.5%, p<0.05), anaerobic power (6.6 vs 1.9%, p<0.05), vertical jump height (3.46 vs 1.54%, p<0.05), explosive power (4.48 vs 3.72%, p<0.05), 20-m sprint (2.4 vs 0.98%, p<0.05) and change of direction abilities (0.9 vs 0.7%, p<0.05). This study indicated that the prolonged competition season might induce significant functional improvements in the physical fitness profile of female volleyball players competing in the regional division.